2019
DOI: 10.1038/s41419-019-1973-7
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Notch-ATM-abl axis by geranylgeranyl diphosphate synthase inhibition

Abstract: Notch proteins drive oncogenesis of many cancers, most prominently T-cell acute lymphoblastic leukemia (T-ALL). Because geranylgeranylated Rab proteins regulate Notch processing, we hypothesized that inhibition of geranylgeranyl diphosphate synthase (GGDPS) would impair Notch processing and reduce viability of T-ALL cells that express Notch. Here, we show that GGDPS inhibition reduces Notch1 expression and impairs the proliferation of T-ALL cells. GGDPS inhibition also reduces Rab7 membrane association and dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Agabiti et al . reported that geranylgeranyl diphosphate synthase, which is an enzyme in the isoprenoid biosynthesis pathway that produces a pathway that produces GGPP, reduces the expression of Notch1 and affects the expression of its downstream target, c-Myc 47 .…”
Section: Discussionmentioning
confidence: 99%
“…Agabiti et al . reported that geranylgeranyl diphosphate synthase, which is an enzyme in the isoprenoid biosynthesis pathway that produces a pathway that produces GGPP, reduces the expression of Notch1 and affects the expression of its downstream target, c-Myc 47 .…”
Section: Discussionmentioning
confidence: 99%
“…DGBP was also found to induce apoptosis in T‐cell acute lymphoblastic leukaemia (T‐ALL) cell lines. 200 A potential mechanism was postulated, connecting disruption of Rab7 localisation due to GGPP depletion with inhibition of Notch1 expression. 201 Notch1 is altered in over 60% of T‐ALL cases and has been shown to promote proliferation and differentiation.…”
Section: Therapeutic Effects Of Ggdps Inhibitorsmentioning
confidence: 99%
“…Addition of GGPP following DGBP treatment was shown to abrogate the anti‐proliferative effects, indicating GGPP depletion to be the key mechanism underlying DGBP effects. DGBP was also found to induce apoptosis in T‐cell acute lymphoblastic leukaemia (T‐ALL) cell lines 200 . A potential mechanism was postulated, connecting disruption of Rab7 localisation due to GGPP depletion with inhibition of Notch1 expression 201 .…”
Section: Therapeutic Effects Of Ggdps Inhibitorsmentioning
confidence: 99%
“…In addition to the above studies, there are other experimental protocols targeting NOTCH1 [51,52], such as the proteasome inhibitor (bortezomib) [53], histone deacetylase inhibitor (panobinostat) [54], HSP90 inhibitor [55,56], insecticide (mebendazole) [57], geranylgeranyl diphosphate synthase inhibition (digeranyl bisphosphonate, DGBP) [58], and the antibody Rova-T against its ligand DLL3 [ 59 ] . Other natural anti-NOTCH compounds have been shown to inhibit NOTCH1 mutant T-ALL cells, such as plant polyphenol flavonoids [60], artemisinin [61], etc.…”
Section: Other Agentsmentioning
confidence: 99%